Culture and Sexual Medicine: A Road Map for Clinical Inquiry and Practice. Issue 9 (25th June 2021) - Bober, Sharon L.; Chevalier, Lydia L.
ABSTRACT: As the field of sexual medicine continues to grow, there has been increasing attention to the importance of the sociocultural components of the biopsychosocial model. Although important in all medical practice, culture and sexual health are particularly entwined, so engaging with sociocultural aspects of the patient experience as part of evaluation and treatment is necessary to optimize patient outcomes in this field. We invite clinicians to consider the importance of sexual health literacy, cultural humility, and support for patient volition as key aspects of moving care towards a model that embraces all aspects of the biopsychosocial model. The aim of the current paper is to provide readers with concrete steps and illustrative examples to help guide this process.